STYLISTIC ANALYSIS ON ROALD DAHL’S POEM TELEVISION - Dewi Max, Jonathan Irene Sartika (Fakultas Ilmu Budaya, Universitas Mulawarman, 2020)
The effect of a poem is deliberately designed by the poet to make it meaningful and emotionally attach the reader. Just like Television poem by Roald Dahl which employs the language features, puts them as foreground, and affects the readers in meaning making. The structure and figurative languages in the poem creates the tone that can raise people awareness of the bad impact of television for children growth and on the other hand gently reminds today’s parents about the goodness of reading books. This study gives empirical evidences of such impression by showing the poetic devices and the language features applied by the poet.